A child with duchenne muscular dystrophy: A case report of a rare diagnosis in Cumilla, Bangladesh (Central Medical College Journal, 2025)
Background: Muscular dystrophies encompass a diverse range of conditions that share the common feature of gradually worsening muscle weakness. Among these, Duchenne Muscular Dystrophy (DMD) stands out as the most prevalent X-linked form affecting children, usually manifesting in the early years of life. This condition primarily weakens muscles near the body's core and causes distinctive calf muscle enlargement in boys. Children with DMD typically show delayed motor milestones and progressive deterioration and ultimately bedbound. The condition often leads to early death due to cardiac or respiratory complications. Current interventions, including corticosteroid therapy and respiratory support, have enhanced daily functioning, mobility duration, overall well-being, and survival rates. However, researchers continue pursuing novel treatments in hopes of finding a definitive cure for this serious disease. This report presents the clinical case of a boy aged 10 years and 11 months diagnosed with DMD, focusing on his distinctive clinical presentation and other significant findings.Central Medical College Journal Vol 9 No 1 January 2025 Page: 53-56